KURIKULUM MERDEKA : STRATEGI IMPLEMENTASI DI SEKOLAH DASAR - Rijkiyah, Dariyatul; Farhurohman, Oman; Habudin, Habudin (Jurnal keilmuan dan Kependidikan dasar, 2023)
One way to overcome the learning deficit caused by the Covid-19 pandemic is through the Independent Curriculum. This aims to change the curriculum so that students' interests and skills will be honed so that they can concentrate on building critical knowledge, moral qualities and student competencies. The aim of this research is to find out more about the implementation of the independent curriculum at SDN 13 Serang, identify the challenges faced by teachers there, and study the strategies teachers apply to overcome these challenges. Descriptive qualitative research methodology was used in this research. Research findings show that the SDN 13 Serang school has succeeded in incorporating the independent curriculum into its teaching methods, although there are a number of challenges faced during this process. The school community's acceptance of the independent curriculum is an aspect that contributes to its implementation. Apart from limited references and unequal access to learning, teachers have additional challenges in implementing an independent curriculum, one of which is the lack of infrastructure to support it. In addition, because the school emphasizes learning according to independent curriculum standards, its use has a very positive impact.